EFEKTIVITAS PEMBELAJARAN MATEMATIKA MELALUI PENERAPAN MODEL KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) - Sape, Herwandi; Habiba Ulfahyana (Jurnal Penalaran dan Riset Matematika, 2023)
This study is a pre-experimental research involving one experimental class that aims to determine the effectiveness of the Teams Games Tournament (TGT) type cooperative learning model in learning mathematics in class XI SMA PGRI Kota Makassar. The research design used was one group pretest-posttest design. The population in this study were all 11th grade students of PGRI Tamalate II High School in Makassar City in the second semester of the 2022/2023 school year, then determining the sample with the Simple Random Sampling technique so that the XI.A class students were selected as the research sample. The instrument used in this study was a learning outcome test to determine the completeness of learning outcomes. The data collection technique used is a learning outcome test given to students at the end of the subject matter. In this study, two statistical analysis techniques were used, namely descriptive statistical analysis and inferential statistical analysis. Based on the results of data analysis, it was found that descriptively the mathematics learning outcomes achieved by XI grade students of SMA PGRI Tamalate II Kota Makassar after applying the Teams Games Tournament (TGT) cooperative learning model were included in the high category with an average value of 82.91 and achieved classical completeness of 92%. Inferentially shows the sign value = 0.000 < α = 0.05, meaning that H0 is rejected and H1 is accepted, in other words, the Teams Games Tournament (TGT) type cooperative learning model is effectively applied in learning mathematics in class XI SMA PGRI Kota Makassar.